History of the Relationship Between the Polish and the Hungarian Nobility in the Light of Old Polish Historical and Geographical Writings in the 18th Century - Wolański, Filip (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
Polish-Hungarian contacts have a tradition dating back to the Middle Ages, which was present in Polish historiography of the early modern times. Knowledge on this subject was present in the consciousness of the Old Polish society. About it was described in medieval chronicles and historical writings of the Renaissance. In the 18th century, Old Polish historiography changed under the influence of the Enlightenment. The historiography was also influenced by the experiences related to the partitions of Poland. The aim of the article is to how the descriptions of Polish-Hungarian relations evolved. Particular attention is paid to the description of the relations between the elites of both countries. Historiographic works and geographical compendiums were used to conduct the study.